Extracting structure functions of power devices in induction motor drives - Aliyu, Attahir Murtala; Castellazzi, Alberto (2016)
This paper proposes the extraction of structure function from power devices on-board induction motor drives. It puts forward the issues and methodology related to on-board measurement of the cooling curve and derivation of the structure function during idle times in induction motor drives for maintenance purposes. The structure function uses the thermal resistances and capacitances in the Cauer form to identify changes in the device structure. The advantage of the structure function is that it does not only reveal the value but also the location of the thermal resistance and capacitance in the heat flow path. The novelty in this work is the methodology used to achieve the measurement of the cooling curve and the derivation of the structure function despite issues related to freewheeling current due to energy stored as a result of motor inductance.